Study of the synergistic influence of zwitterionic interactions and graphene oxide on water diffusion mechanism and mechanical properties in hybrid hydrogel network. (February 2023) - Hashmi, Saud; Ahmed, Rafiq; Rehman, Adeel ur; García-Peñas, Alberto; Zahoor, Awan; Khan, Firoz; Vatankhah-Varnosfaderani, Mohammad; Alshahrani, Thamraa; Stadler, Florian J.
Abstract: Hybrid hydrogels based on n-isopropylacrylamide, zwitterionic comonomer, and graphene oxide were synthesized to study their physical and mechanical properties. The compositional variation largely influenced the swelling characteristics of the hybrid hydrogels compared to mechanical properties, i.e., elongation and compression. Additionally, Rheometric swelling measurements on the swollen hydrogels were performed until they reached equilibrium showed a very low phase angle δ indicating strong covalent network, which intrun increases with increasing content of zwitterions and GO. Swelling kinetics were studied and found to follow Fickian dynamics, albeit zwitterion-containing gels showed a peculiar 2-step swelling pattern. Interestingly, differences in the swelling mechanism are also clear for the hydrogels with 2D GO (Graphene oxide) nano-fillers from its 1D nano-filler CNTs (Carbon nanotubes). In elongation, the samples break in a brittle fashion at Hencky strains ε max around 0.4–0.65 with the maximum stress being observed for samples with high Zw-content and 0.2% GO, which can be explained by the stress-rising properties of sharp edges of GO. In contrast, the data in compression profits from higher GO-contents as crack growth is less important in this deformation mode. This work will contribute to future composite gel applications. Graphical abstract: Image 1 Highlights: Hybrid hydrogels based on PNIPAM, zwitterionic comonomer and GO were synthesized. Hybrid hydrogels were tested under rheometric swelling in elongation and compression. Water diffusion and swelling mechanism support the mechanical characterization.